EWSR1‐PBX3 gene fusion in cutaneous syncytial myoepithelioma. (3rd April 2019) - MacKinnon, William F.; Carter, Michael D.; Bridge, Julia A.; Tremaine, Robert D.; Walsh, Noreen M.G.
Abstract : Cutaneous syncytial myoepithelioma (CSM) is a recently recognized, histopathological variant of myoepithelial (ME) tumors of the skin. It is characterized by a syncytial arrangement of spindled, ovoid, and/or epithelioid cells forming a well‐circumscribed, unencapsulated dermal nodule. There is a paucity of intervening stroma, and absent duct or gland formation. Strong immunohistochemical staining for S100 and epithelial membrane antigen (EMA) has been described, while cytokeratin expression has been uncommon. The majority of CSMs harbor a rearrangement involving the EWSR1 gene. Although various fusion partner genes have been discovered in ME tumors at other anatomic sites, none has yet been described in CSM. We present a case of CSM represented clinically by a papule on the mid‐upper back of a healthy 44‐year‐old female. It exhibited morphological and immunohistochemical features of a CSM with strong, diffuse S100 and alpha‐actin expression, and focal positivity for EMA and cytokeratin AE1/AE3. Fluorescence in‐situ hybridization showed an EWSR1 gene rearrangement. Massively parallel next‐generation RNA sequencing revealed PBX3 as the fusion partner. The EWSR1‐PBX3 gene fusion has been previously identified in three cases of ME tumors of bone and soft tissue, and in a case of retroperitoneal leiomyoma. This is the first report of an EWSR1‐PBX3 fusion in CSM.